Successful treatment for psychomotor agitation in neuromyelitis optica spectrum disorder with trazodone–risperidone combination: a case report - Narita Z (Dove Medical Press, 2017)
Zui Narita,1 Harumasa Takano,1 Tomiki Sumiyoshi2 1Department of Psychiatry, National Center Hospital, 2Department of Clinical Epidemiology, Translational Medical Center, National Center of Neurology and Psychiatry, Tokyo, Japan Abstract: Neuromyelitis optica (NMO) is a relapsing disease that typically affects the spinal cord and optic nerves. So far, a few studies have reported pharmacologic treatment for psychiatric symptoms in patients with NMO spectrum disorder (NMOSD). However, no literature has described psychomotor agitation associated with the disease and its treatment. We report an 84-year-old woman with NMOSD whose psychomotor agitation was effectively treated with a combination of trazodone and risperidone. Our observation suggests the ability of augmentation of antipsychotic drugs with antidepressants to ameliorate psychotic symptoms associated with NMOSD. Keywords: neuromyelitis optica, multiple sclerosis, psychomotor agitation, trazodone, risperidone